An Experimental Study on Possible Interactions and Collaborations Between Industrial Design Education and Startup Ecosystem - Ozan Soyupak; H. Hümanur Bağlı (Anı Publishing, 2020)
Industrial design departments usually make collaborative projects with large scale firms and SMEs. In this research, absence of a similar collaborative relationship between startups and industrial design education is seen as a problem and a potential. Main objective of this research is to examine the interaction and collaboration possibilities between startups and industrial design education. In order to do that, experimental relationships have been set between industrial design and startups. Data collected through triangulation method and were analyzed in a four staged process. At first, related concepts to be advanced in coding process was obtained by literature review and gathered data. After coding, concepts were categorized under themes. At this stage, data were revised for internal and external consistency. For the last, findings were interpreted and analysed. MAXQDA 12 was used to analyze qualitative data. With the help of this research, a link between business and entrepreneurship literature, and industrial design literature was established. Need for the information related with design and design thinking application in startups were tried to be answered by the experimental studies of this research.